Relative Wear of Enamel Opposing Low-Fusing Dental Porcelain - Nancy L. Clelland, DMD, MSD,1 Vaishali Agarwala, DDS,2 (Journal of Prosthodontics, 2003)
This study evaluated the wear of human enamel opposing 5 low-fusing dental porcelains and a traditional feldspathic control.